2010
DOI: 10.1159/000322086
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiving in Dementia: The Asian Perspective of a Global Problem

Abstract: Background/Aims: With an increasing life expectancy, the number of people suffering from dementia globally will rise to about 115.4 million by 2050. It is projected that in the 21st century, the majority of the world’s older people will be living in Asia. This paper examines the global issues of family caregiving for older persons with dementia from an Asian perspective. Methods: Literature review of published empirical studies from 1990 to October 2010. Results: A full understanding of the specific way that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
146
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 123 publications
10
146
0
3
Order By: Relevance
“…Culture may also determine how they talk about mental illness (Helman, 1990). A review of cross-cultural psychiatry revealed that the use of cultural idioms, albeit scant, was found in insightful studies of schizophrenia (Yang, 2007;Yang & Kleinman, 2008;Yang, Phillips, Lo, Chou, Zhang & Hopper, 2010); dementia (Ikels, 1998) and Alzheimer's disease (Chan, 2010). Yang and colleagues (2010) reported that cultural idioms were functional in helping participants to express culturally relevant feelings and recognize culturally abnormal behaviors.…”
Section: Our Present Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Culture may also determine how they talk about mental illness (Helman, 1990). A review of cross-cultural psychiatry revealed that the use of cultural idioms, albeit scant, was found in insightful studies of schizophrenia (Yang, 2007;Yang & Kleinman, 2008;Yang, Phillips, Lo, Chou, Zhang & Hopper, 2010); dementia (Ikels, 1998) and Alzheimer's disease (Chan, 2010). Yang and colleagues (2010) reported that cultural idioms were functional in helping participants to express culturally relevant feelings and recognize culturally abnormal behaviors.…”
Section: Our Present Studymentioning
confidence: 99%
“…Dementia was identified as a 'mind stealer' (Ikels, 1998, p. 257). It was perceived as a result of not being open-minded enough (Chan, 2010). According to Chan (2012), Alzheimer's disease was considered by some people in Hong Kong as the destiny of heaven (tien ming) (p. 472).…”
mentioning
confidence: 99%
See 3 more Smart Citations